Uso de dispositivos auxiliares para audição e fluência na libras e na língua oral de estudantes surdos da cidade de Belo Horizonte - Erika Fernanda Clark (2021)
Introduction: This study aims to evaluate the relationship between the use of hearing aid devices and fluency in Libras and the oral language of deaf students from the perspective of the translators/interprets who accompanied those students. Methods: This is a cross-sectional observational study. The data were collected at the Association of the Deaf of Minas Gerais, an organization that serves the Belo Horizonte Municipal Education Department. Participated 112 employees, of which 76 Libras translators/interpreters and 36 Libras instructors, who answered a questionnaire with sociodemographic information, auditory characteristics, fluency in Libras, and oral language of the students. The deaf students included were those enrolled in the Belo Horizonte municipal school system attended by professional translators/interpreters. The analysis of the association between fluency in Libras and oral language and the use of hearing aid was performed using the Chi-square test. The analysis of the association between fluency in Libras and fluency in the oral language was performed using the McNemar test. Results: Libras translators / interpret and instructors' responses referred to 126 (87%) deaf students enrolled. The degree of hearing loss of students was mild/moderate in 28 (22%) and severe/profound in 98 (78%). Of the 126 includes, 83 (66%) had fluency Only in Libras, 12 (10%) only in oral language, 18 (14%) in Libras and oral language, and 13 (10% had no fluency in any language. Concerning auxiliary electronic hearing devices, 57 (45%) students used them. A statistical association was observed between the use of a hearing aid and oral fluency (p<0.001) and between fluency in Libras (p=0.032). Oral fluency and Libras fluency were associated, and of the total students fluent in the oral language, 18 (60%) were also fluent in Libras (p<0,001). Conclusion: Libras was the communicative modality used mostly by students fluent in Libras and fluent in the oral language. Even students using electronic devices preferred Libras to communicate. This data indicates the importance of Libras for the development of fluency in students' oral language using electronic devices.